Key multiplicity issues in clinical drug development. (9th October 2012) - Dmitrienko, Alex; D'Agostino, Ralph B.; Huque, Mohammad F.
<x xml:space="preserve">Abstract</x> Much progress has been made over the past decade with the development of novel methods for addressing increasingly more complex multiplicity problems arising in confirmatory Phase III clinical trials. This includes traditional problems with a single source of multiplicity, for example, analysis of multiple endpoints or dose–placebo contrasts. In addition, more advanced problems with several sources of multiplicity have attracted attention in clinical drug development. These problems include two or more families of objectives such as multiple endpoints evaluated at multiple dose levels or in multiple patient populations. This paper provides a review of concepts that play a central role in defining and solving multiplicity problems (error rate definitions) and introduces main classes of multiple testing procedures widely used in clinical trials (nonparametric, semiparametric, and parametric procedures). The paper also presents recent advances in multiplicity research, including gatekeeping procedures for clinical trials with multiple sets of objectives. The concepts and methods introduced in the paper are illustrated using several case studies on the basis of real clinical trials. Software implementation of commonly used multiple testing and gatekeeping procedures is discussed. Copyright © 2012 John Wiley & Sons, Ltd.